Vitamin D status among adults in the Aegean region of Turkey - Güçlü Feyzullah; Pala Tümer; Güvenç Yesim; Onur Ece; Kafesçiler Sabriye; Dinç Gönül; Hekimsoy Zeliha; Özmen Bilgin (BMC, 2010)
Abstract Background Vitamin D is a lipid-soluble hormone found in certain foods and synthesized from precursors in the skin when exposed to ultraviolet light. Vitamin D plays a critical role in bone metabolism and many cellular and immunological processes and low levels have been associated with several chronic and infectious diseases. Vitamin D status is assessed by measuring the concentration of serum 25-hydroxyvitamin D [25(OH)D]. Vitamin D deficiency is reported to be common worldwide, but little has been reported about the vitamin D status of adults in Turkey. In this cross-sectional study, we determined the prevalence of 25(OH)D deficiency in adults residing in a city in the Aegean region of Turkey. Methods A survey was conducted on a representative sample of adults over 20 years old in a non-coastal city at the end of the winter season. Of the 209 households selected by random sampling, 8.6% (n = 18) were unoccupied and 21.5% (n = 45) refused to participate. Blood samples were taken and questions about medical history, vitamin supplementation, sunlight exposure, and dietary calcium and vitamin D intake were asked in face-to-face interviews of 391 adults living in the remaining households. Results The mean serum 25(OH)D concentration was 16.9±13.09 ng/mL, with 74.9% of the subjects having 25(OH)D deficiency (<20 ng/mL), 13.8% having insufficiency (20-29.99 ng/mL), and 11.3% of the subjects having sufficient 25(OH)D (≥30 ng/mL) levels. 25(OH)D deficiency was more common among females (78.7%) than males (66.4%, p < 0.05). Conclusion Adults living in an urban, non-coastal setting in Turkey have a high prevalence of vitamin D deficiency.